The Role of Helper T Cells in Psoriasis - Hu, Peng; Wang, Mengyao; Gao, Hu; Zheng, Ai; Li, Jinhui; Mu, Dezhi; Tong, Jiyu (Frontiers in Immunology, 2021)
Psoriasis is a complex, chronic relapsing and inflammatory skin disorder with a prevalence of approximately 2% in the general population worldwide. Psoriasis can be triggered by infections, physical injury and certain drugs. The most common type of psoriasis is psoriasis vulgaris, which primarily features dry, well-demarcated, raised red lesions with adherent silvery scales on the skin and joints. Over the past few decades, scientific research has helped us reveal that innate and adaptive immune cells contribute to the chronic inflammatory pathological process of psoriasis. In particular, dysfunctional helper T cells (Th1, Th17, Th22, and Treg cells) are indispensable factors in psoriasis development. When stimulated by certain triggers, antigen-presenting cells (APCs) can release proinflammatory factors (IL-23, IFN-α and IL-12), which further activate naive T cells and polarize them into distinct helper T cell subsets that produce numerous cytokines, such as TNF, IFN-γ, IL-17 and IL-22, which act on keratinocytes to amplify psoriatic inflammation. In this review, we describe the function of helper T cells in psoriasis and summarize currently targeted anti-psoriatic therapies.